Hemoglobin mass after 21 days of conventional altitude training at 1816 m - Pottgiesser, T.; Ahlgrim, C.; Ruthardt, S.; Dickhuth, H. H.; Schumacher, Y. O. (Journal of Science and Medicine in Sport, 2009)
The underlying mechanisms of altitude training are still a matter of controversial discussion but erythropoietic adaptations with an increase of total haemoglobin mass (tHb) have been shown in several studies, partly depending on an adequate hypoxic dose. The aim of this retrospective study was to investigate if a 3 weeks sojourn at moderate altitude (1816 m) with conventional training sessions (live and train at moderate altitude), especially under real and uncontrolled conditions, results in an increased tHb. tHb was measured in seven male cyclists competing at elite level (German national cycling team, U23 category) prior to the ascent to altitude and immediately after descent to sea-level. The athletes completed a 21 days altitude training camp living at 1816 m and training at 1800-2400 m during the competitive season. No significant difference was found in tHb after the altitude sojourn (prior 927 ± 109 g vs. 951 ± 113 g post, 95% CI -13-61 g). Additionally, the analysis of red cell volume, plasma volume and blood volume or haemoglobin concentration [Hb] as well as haematocrit (Hct) did not reveal any significant changes. The data supports the theory that an adequate hypoxic dose is required for adaptations of the erythropoietic system with an increase of tHb and a threshold of approximately 2100-2500 m has to be exceeded.